Study on the passive mode-locking of Nd:GdVO4 laser - Lim, Kang Wei. (2010)
Laser, which means Light Amplification by the Stimulated Emission of Radiation, is a piece of equipment that generates and amplifies light. The aim of this project is to investigate experimentally the lasing property of a diode end-pumped Nd:GdVO4 solid-state laser and to generate mode-locked pulses through passive mode-locking. A laser was set up and its operation was investigated. In order to produce mode-locked pulses, a semiconductor saturable absorber was introduced into the cavity. Measurements were taken from the output beam. From the experiment, we will demonstrate the stable high-power continuous wave mode-locking in the diode-pumped Nd:GdVO4 crystal laser.